PREVALENCE OF METABOLIC SYNDROME AND ITS COMPONENTS IN WOMEN WITH SUBCLINICAL HYPOTHYROIDISM - Pangaluri, Renuka; S, Akila; William, Ebenezer (Asian Journal of Pharmaceutical and Clinical Research, 2013)
Objective: Thyroid dysfunction was found to be more common among women with metabolic syndrome. A cross-sectional analysis showed that subjects with subclinical hypothyroidism (SH) had high prevalence of cardiovascular disease than euthyroid subjects. The objective of the current study is to evaluate the prevalence of metabolic syndrome and cardiovascular risk factors among subclinical hypothyroid subjects. Methods: Thirty untreated subclinical hypothyroid women and thirty normal healthy subjects were recruited for the study. Fasting blood samples were collected for lipid profile, glucose and insulin level estimation. Results: Fasting plasma glucose, total cholesterol, triglycerides and LDL-cholesterol were found to be significantly increased in SH patients Both systolic and diastolic blood pressures were higher in the patient group. 43.3 percent of the SH patients were found to satisfy the criteria for metabolic syndrome. Conclusion: In our study, subclinical hypothyroidism is significantly associated with metabolic syndrome and its components. Whether this association might be translated into a compounded cardiovascular risk needs to be evaluated by further studies. Key Words: Subclinical hypothyroidism, metabolic syndrome, cardiovascular risk.